Antibacterial and cytotoxic activity of Tamarindus indica (Tamarind) seeds - Hasan, MM; Rahman, SA; Akhter, MS (Journal of Bio-Science, 2019)
The crude ethanol and methanol extracts of Tamarindus indica seeds have been investigated to evaluate their antibacterial and cytotoxic potentialities. Extracts were screened for their antibacterial activity against both gram positive and negative bacteria primarily by disc diffusion method and then minimum inhibitory concentration (MIC) assay. Besides the cytotoxic activity were screened by using brine shrimp lethality bioassay. The average zone of inhibition for ethanol extract of seeds of tamarind was ranged from 7.5 - 13.5 mm for 500 μg/disc. And for methanol extract the zone of inhibition was ranged from 6.5 - 13.25 mm for 500 μg/disc. From MIC assay minimum inhibitory concentration was found 1.25 mg/ml for ethanol and 0.625 mg/ml for methanol extract. The minimum bactericidal concentration was found 2.5 mg/ml for ethanol and 1.25 mg/ml for methanol extract. Compared to vincristine sulfate (with LC50 of 0.99 μg/ml) both ethanol and methanol extract of T. indica seeds showed toxicity lower than 100 μg/ml and greater than 30 μg/ml. The study confirms greater antibacterial activity of T. indica seed extracts with moderate cytotoxic activity. This study thus demands isolation of active principles and thorough bioassays. J. bio-sci. 27: 83-88, 2019